Social business and sustainable development (Desenvolvimento em Questão, 2023)
Sustainable entrepreneurship has been debated recently, as organizations are combining their economic efforts with actions in favor of social and environmental well-being. The concept of social businesses emerges in society, self-sustaining organisms, which have a positive impact through the implementation of socio-environmental projects and generate revenues like any other company within the traditional capitalist logic. Thus, the main objective of the article is to analyze how sustainable development is carried out in social businesses, through an exploratory and descriptive study in digital sources, analyzing a sample of social businesses with the presentation of their actions and services and which ones Sustainable Development Goals (SDGs) are in agreement. As a methodology, this research follows a qualitative approach. As for the purposes, it is exploratory and descriptive, as for the means, field research was carried out on the websites of ten companies located in the state of Rio de Janeiro. The research method was based on content analysis. The main results indicate that companies perform actions such as reverse logistics, recycling, composting, soil recovery and replanting. They also present certain characteristics such as socio-environmental culture, qualification of labor, identity, gender equality, skills and attitudes aimed at environmental conservation. It is concluded that social businesses need to become increasingly professional and pay attention to the most modern management practices in the current market, as there is still a lack of knowledge and attitude to bring about changes in the administrative, financial and strategic areas.
Keywords: Sustainable entrepreneurship; Social Business; Sustainable development.